2010
DOI: 10.1007/s00442-010-1599-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in response to phosphorus and light availability in four forest herbs

Abstract: The differential ability of forest herbs to colonize secondary forests on former agricultural land is generally attributed to different rates of dispersal. After propagule arrival, however, establishing individuals still have to cope with abiotic soil legacies from former agricultural land use. We focussed on the plastic responses of forest herbs to increased phosphorus availability, as phosphorus is commonly found to be persistently bioavailable in post-agricultural forest soils. In a pot experiment under fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Likewise, Baeten et al (2009a) showed that the contrasting land-use history of forest stands was reflected in the plant P concentrations of two forest herbs (P. elatior, G. urbanum). Furthermore, the plastic response of forest herbs to increased P availability we found here partly generalizes the results from pot experiments (Pigott and Taylor 1964;Hipps et al 2005;Baeten et al 2010) to field conditions and a larger set of species. The first hypothesis thus seems to hold regarding the plant P concentration.…”
Section: Land-use Effects On Plant Nutrient Concentrationssupporting
confidence: 68%
See 4 more Smart Citations
“…Likewise, Baeten et al (2009a) showed that the contrasting land-use history of forest stands was reflected in the plant P concentrations of two forest herbs (P. elatior, G. urbanum). Furthermore, the plastic response of forest herbs to increased P availability we found here partly generalizes the results from pot experiments (Pigott and Taylor 1964;Hipps et al 2005;Baeten et al 2010) to field conditions and a larger set of species. The first hypothesis thus seems to hold regarding the plant P concentration.…”
Section: Land-use Effects On Plant Nutrient Concentrationssupporting
confidence: 68%
“…If land-use history affects the composition and structure of the canopy, e.g. with higher light availability in post-agricultural sites, this might also account for the observed plasticity in biomass production for species such as U. dioica, A. podagraria and G. urbanum (Pigott and Taylor 1964;Elemans 2004;Baeten et al 2010). The relative importance of light availability was, however, not explicitly determined here.…”
Section: Land-use Effects On Aboveground Plant Biomassmentioning
confidence: 60%
See 3 more Smart Citations